Algerian contribution to international sporting events: findings and perspectives - Nasredine, GUEMRICHE; Abdelatif, HOUAR (Journal of Sport Science Technology and Physical Activities, 2021)
Algeria becomes aware of the sport weight as political tool in the service of its relations with the world. Otherwise, the sport worldwide process has lead to the creation of a vast number international organization with various status, favoring competitions proliferation, developing some forms of cooperation, but orchestrating nevertheless a power distribution according to the influence sphere, embracing perfectly the logic of the dominating world economic order. A non-exhaustive census of some Algerian representatives within the international sport authorities shows that among the 92 concerned persons, thirty are executive organ members of the institutions. In spite of the noticeable representation, we mustabe set in evidence the constraint. Lie heavy in the postulants during the election to the international sport authorities.